2011
DOI: 10.3354/meps09061
|View full text |Cite
|
Sign up to set email alerts
|

Food availability effects on reproductive strategy: the case of Acartia tonsa (Copepoda: Calanoida)

Abstract: Food availability has been linked to changes in the biochemical composition of zooplankton eggs. However, a number of species are capable of resource storage and are thereby able to use accumulated reserves for reproduction during periods of poor food conditions. Conversely, in species such as Acartia tonsa with limited storage capacities, there can be a strong dependence of egg composition on ambient food conditions. The aim of this study was to determine the effect of food availability on the carbohydrate, p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 53 publications
2
4
0
Order By: Relevance
“…In this way, our study confirms the hypotheses proposed by Paschke et al (2004) and provides a chemical basis explaining the previously observed seasonal patterns in larval starvation resistance. Similar seasonal variations in offspring quality and environmental conditions prevailing at hatching have also been described in other aquatic crustacean species, for example in porcelain crab (Gebauer et al 2010), marine copepods (Acheampong et al 2011) and limnic cladocerans (Boersma 1997).…”
Section: Discussionsupporting
confidence: 70%
“…In this way, our study confirms the hypotheses proposed by Paschke et al (2004) and provides a chemical basis explaining the previously observed seasonal patterns in larval starvation resistance. Similar seasonal variations in offspring quality and environmental conditions prevailing at hatching have also been described in other aquatic crustacean species, for example in porcelain crab (Gebauer et al 2010), marine copepods (Acheampong et al 2011) and limnic cladocerans (Boersma 1997).…”
Section: Discussionsupporting
confidence: 70%
“…Laboratory experiments have demonstrated that resting egg production can be induced by both food and temperature, as well as by photoperiod, abrupt salinity changes, crowding and oxygen deficiency (Uye et al, 1979;Sullivan and McManus, 1986;Ban and Minoda, 1994;Chinnery and Williams, 2003;Holmstrup et al, 2006;Holste and Peck, 2006;Drillet et al, 2011). It has also been suggested that the higher protein content of resting eggs from A. tonsa produced under starvation is an indication of resting eggs being an adaption to cope with low food availability (Acheampong et al, 2011). In the present study resting eggs are viewed as an adaption to seasonality, which is why seasonal range and not actual values of chlorophyll a concentrations or SST is related to their production.…”
Section: Factors Influencing Resting Eggsmentioning
confidence: 99%
“…These changes have most likely reduced the lipid content in zooplankton available for clupeids as Pseudocalanus sp. is characterized by lipid storage in large oil sacs, while species such as Acartia tonsa have limited storage capacity (Acheampong et al, 2011). Furthermore, mysids, an alternative prey for herring, occur in low abundance in the central Baltic possibly due to inaccessibility of the oxygen-deficient bottom layer (Barz and Hirche, 2009).…”
Section: Effects Of Ecosystem Changes On Lipid Content In Forage Fishmentioning
confidence: 99%